Genetic resistance to endoparasites in sheep and goats. A review of genetic resistance to gastrointestinal nematode parasites in sheep and goats in the tropics and evidence for resistance in some sheep and goat breeds in sub-humid coastal Kenya - Baker, R.L. (Cambridge University Press, 1998)
The evidence for both between-and within-breed genetic variation for resistance to gastrointestinal (GI) nematode parasites is reviewed. It is concluded that much of the published research on breed characterisation for resistance suffers from poor experimental design. Prior to the initiation of a 6-year study that has just been completed in coastal Kenya there were no estimates of within-breed genetic variation (i.e. heritabilities) of resistance in sheep or goats in the tropics. This study has confirmed that Red Maasai sheep and Small East African (SEA) goats are more resistant to GI parasites (predominantly Haemonchus contortus) than Dorper sheep and Galla goats. Heritability estimates for logarithm transformed faecal egg counts (an indicator of resistance) in 8-month-old lambs was 0.18 (+ or-) 0.08 for all lambs, but higher in the susceptible Dorper-sired lambs (0.35 (+ or-) 0.16) than in the resistant Red Maasi-sired lambs (0.06 (+ or -) 0.07). This difference in heritability suggests that many centuries of natural selection have fixed most of the genes for resistance in the Red Maasai sheeThe resistant Red Maasai sheep and SEA goats were two to three times more productive than the susceptible Dorper sheep and Galla goats in the sub-humid coastal Kenya environment.